Recommendations of the ESSR Arthritis Subcommittee for the Use of Magnetic Resonance Imaging in Musculoskeletal Rheumatic Diseases - Sudoł-Szopińska, Iwona; Jurik, Anne Grethe; Eshed, Iris; Lennart, Jans; Grainger, Andrew; Østergaard, Mikkel; Klauser, Andrea; Cotten, Anne; Wick, Marius C.; Maas, Mario; Miese, Falk; Egund, Niels; Boutry, Nathalie; Rupreht, Mitja; Reijnierse, Monique; Oei, Edwin H. G.; Meier, Reinhard; O'Connor, Phil; Feydy, Antoine; Mascarenhas, Vasco; Plagou, Athena; Simoni, Paolo; Platzgummer, Hannes; Rennie, Winston J.; Mester, Adam; Teh, James; Robinson, Philip; Guglielmi, Giuseppe; Åström, Gunnar; Schueller-Weiderkamm, Claudia (Seminars in Musculoskeletal Radiology, 2015)
This article presents the recommendations of the European Society of Musculoskeletal Radiology Arthritis Subcommittee regarding the standards of the use of MRI in the diagnosis of musculoskeletal rheumatic diseases. The recommendations discuss (1) the role of MRI in current classification criteria of musculoskeletal rheumatic diseases (including early diagnosis of inflammation, disease follow-up, and identification of disease complications); (2) the impact of MRI on the diagnosis of axial and peripheral spondyloarthritis, rheumatoid arthritis, and juvenile spondyloarthritis; (3) MRI protocols for the axial and peripheral joints; (4) MRI interpretation and reporting for axial and peripheral joints; and finally, (5) methods for assessing MR images including quantitative, semiquantitative, and dynamic contrast-enhanced MRI studies.
Keywords: arthritis; sacroiliitis; spondyloarthritis; magnetic resonance imaging; diagnosis